Direct And Indirect Influence Of Human Resource Management Practices On Employee Outcomes In Service-based Cooperatives In Malaysia - Rajaratnam, Sushila Devi (2007)
This study investigated the direct and indirect influence of human resource management practices on employee performance and turnover intentions. The indirect relationship was investigated by examining the mediating roles of job satisfaction, organisational commitment and supervisory commitment. No published work has investigated the relationships between human resource management practices, job satisfaction, organisational commitment, supervisory commitment, employee performance and turnover intention simultaneously, in the same study.